Cosmic Surgery: Development of a New Non-Invasive Technique in Modern Surgery. - Muhammad Fazlul Islam (International Journal of Surgical Techniques, 2023)
Cosmic surgery is a non-invasive operation developed by applying modern astronomical discoveries to surgical science. Scientific cosmology is the study of the universe through physics and astronomy. Religious cosmology explains the universe based on religious scriptures. According to religious cosmology, the universe consists of hell, heaven, and earth. Earth is surrounded by hell, and hell is surrounded by heaven. Astronomers explored the universe and found billions of galaxies of stars all around the earth made of hellish fire. The location of the stars and hells in the universe and their characteristics are identical. Comparative study shows that all the stars in the visible galaxies of the universe are religious hells. The discovery of hells in the lower universe confirms the existence of heavens in the inaccessible upper universe that has been predicted in the Holy Scriptures. This astronomical discovery is not only a message to mankind but also a recombinant cosmic signal all over the world, which is generated for the exploration of the cosmos by prophets and astronomers. According to the supernatural theory of disease, supernatural virus infects the prefrontal cortex of the human brain and disrupts the normal spirit of executive functions including reasoning, planning, motivation, and problem solving that leads people to a delusional lifestyle and behavior and alters the dynamic equilibrium between man and environment, and causes all physical, mental, social, and spiritual disorders, national, international, and inter-religious conflicts and wars in the world. Cosmic surgery is a non-invasive operation applying above mentioned cosmic signal to the human brain to sterilize the whole world from the supernatural virus that can change our sick world into a healthier, happier, and prosperous world like a terrestrial paradise.
Keywords: Cosmic Surgery